Seawater intrusion studies for coastal aquifers - Saley Abraham (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 1988)
Studies were conducted in three villages along the coastal areas of Trichur district, namely, Nattika, Talikulam and Edamuttam, to know the extent of sea water intrusion through aquifers. Observations were made in existing wells along an alignment normal to the coast line. Aquifer parameters and fresh water flow through the aquifer were computed making use of borehole data available for the region. The positions of the interfaces were determined using established formulae. The possible shifting of the interfaces due to reduction In fresh water discharge consequent to future increased rate of pumping was predicted. In each village, -three wells were taken for the study purpose. In all the cases, the maximum rates of pumping for various depths of wells, which will not cause sea water intrusion problems, have been deter¬mined. Chemical analysis showed that, at present there was no salt water intrusion in the wells under study. The results of the present study lead to a better understanding of the sea water intrusion problem, the determination of the position of the interfaces for various pumping rates might be effectively used in fixing the location of wells, pumping rates and depth of wells. The study would be made use of designing a ground water system in coastal areas for a better utilisation of ground water resources.